ARMBoost+: Empowering stacking, ensemble, and boosting models for network intrusion detection with dynamic rule repository - Vivek, Vullikanti; Veeravalli, Bharadwaj (Journal of network and computer applications, 2025)
As network security threats become increasingly complex, the need for efficient and effective network intrusion detection systems (NIDS) is more important than ever. Machine learning (ML) has emerged as a promising solution for NIDS due to its ability to analyze large volumes of network traffic data and detect suspicious patterns. In this paper, we propose ARMBoost+ a novel integrated approach for NIDS using dynamic rule repository building with a combination of stacking, ensemble, and boosting ML models, and associative rule mining (ARM) and bloom filter techniques. ARMBoost+ approach involves generating frequent feature sets using ARM and building a feature repository using bloom filter to avoid duplicate patterns. We then use the feature repository to train the ML models, which are tested on live network traffic data to generate dynamic rules for the rule repository. The live traffic data allowed us to assess the performance and robustness of our NIDS under dynamic and unpredictable network scenarios. The dynamic rule repository is continuously updated with new attack patterns, ensuring that the NIDS is always up-to-date with the latest security threats. To evaluate the effectiveness of ARMBoost+, we conducted experiments using a publicly available datasets and compared the results to existing NIDS approaches. We tested our approach under various scenarios, including simulating ML models without ARM and without automated feature dropping, and using ARM and bloom filter. We employed several ML models, including Stacking Classifier (with logistic regression (LR), random forest (RF), and support vector machine (SVM)), Ensemble with SVM, AdaBoost with Decision Tree, Gradient Boosting, and XGBoosting. Our experimental results demonstrate that the proposed novel ARMBoost+ integrated approach outperforms existing NIDS approaches in terms of accuracy and detection rates. The combination of stacking, ensemble, and boosting ML models, along with ARM and bloom filter, proved to be highly effective in detecting network intrusions. The dynamic rule repository building approach allowed for continuous updating of the NIDS with the latest attack patterns, resulting in improved performance over time. Furthermore, ARMBoost+ approach showed robustness against various types of attacks, including denial-of-service (DoS) and port scanning attacks. We also observed that the inclusion of ARM and bloom filter resulted notable reduction in the False Positive Rate (FPR) by around 4.07% and improved the efficiency of the feature repository.